Experimental laboratory study on the acoustic response during injection of supercritical CO2 into brine saturated sandstones - Lebedev, Maxim; Mikhaltsevitch, Vassili; Gurevich, Boris (ASEG, 2013)
Quantitative knowledge of the acoustic response of rock from an injection site on supercritical CO2 saturation is crucial for understanding the feasibility of time-lapse seismic monitoring of CO2 plume migration. A suite of sandstones with similar composition but different petrophysical properties has been tested to reveal the effects on acoustic responses of supercritical CO2 injection into brine saturated sandstones. CO2 is first injected into dry samples, flushed out with brine and then injected again into brine saturated samples. Such experimental protocol allows us to obtain acoustic velocities of the samples for the wide range of CO2 saturations from 0 to 100%. On injection of supercritical CO2 (scCO2) into brine-saturated samples, some of samples exhibit observable perturbation of ~10% of compressional velocities with the increase of CO2 saturation form 0% to maximum (~50%). However for some sample effect of scCO2 injection on acoustic properties is negligible.